The Mechanism of Acupuncture Therapy for Migraine: A Systematic Review of Animal Studies on Rats - An Y; Zhang J; Ren Q; Liu J; Liu Z; Cao K (Journal of Pain Research)
Yuqiu An,1,2,* Jing Zhang,1,2,* Qiaosheng Ren,1,2 Jiaojiao Liu,1,2 Zhenhong Liu,1,2,* Kegang Cao1,2,* 1Department of Neurology, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of China; 2Institute for Brain Disorders, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kegang Cao; Zhenhong Liu, Email Kgdoctor@sina.com; lzhh0399@163.comBackground: Acupuncture has long been used for migraine treatment as it is convenient for use and has remarkable efficacy. The acupuncture-based comprehensive treatment plan has been widely recognized for migraine prevention and treatment. However, the mechanism underlying acupuncture efficacy in migraine treatment is not yet completely understood. Our goal is to systematically analyze and evaluate this efficacy mechanism in migraine treatment-related basic research.Methods: To retrieve animal experiments investigating the action mechanism of acupuncture in migraine treatment, We conducted a literature search in major databases, the search period was the inception of each database to April 1, 2024. Literature was screened and data were extracted independently based on predefined inclusion and exclusion criteria. The animal models, acupuncture points, and acupuncture methods specified in the included studies were statistically analyzed and summarized. Furthermore, the potential action mechanisms of acupuncture were discussed.Results: In total, 20 animal experimental studies were included in the present analysis, and all of these studies used rats. In the order of frequency of use, the migraine animal models employed in the searched studies were the dural stimulation model, the nitroglycerin model, and the cortical spreading depression model. The primary acupuncture points selected were Fengchi (GB20) and Yanglingquan (GB34), and electroacupuncture was the most frequently used acupuncture method. The action mechanism of acupuncture underlying migraine treatment primarily involves regulating the descending pain modulatory system and inhibiting neurotransmitters such as CGRP, SP, and 5-HT, as well as microglial cell activation. It also reduces the levels of inflammatory cytokines, thereby mitigating neurogenic inflammation and improving central sensitization.Conclusion: Acupuncture exerts its therapeutic effect on migraine by regulating neurotransmitter release, inhibiting inflammatory responses, modulating central analgesic mechanisms, and suppressing glial cell activation. However, further in-depth exploration is needed in the study of the mechanisms underlying acupuncture treatment for migraine.Keywords: migraine, acupuncture, trigeminal neurovascular system, neurogenic inflammation, neurotransmitter